Effect of Diversity Management on Organizational Performance of Information, Communication and Technology Firms in Nairobi County - Mugwe, Margaret Wangui; Mose, Dr. Thomas Chuma (Human Resource and Leadership Journal, 2020)
Purpose: The study sought to establish the effects of diversity management on organizational performance of ICT firms in Nairobi County. The study specifically sought to establish the effects of creativity and innovation, employee commitment, corporate image and human capital pool on organizational performance of ICT firms in Nairobi County. Methodology: The study targeted ICT firms in Nairobi County categorized into networking, software development, hardware maintenance and distribution, communication and system security. The study adopted a purposive sampling technique to acquire a sample of 15 firms. The unit of observation comprised eight employees per each of the targeted firms thus making a total of 120 respondents. The study used a census survey since the population was small and adequate for study. Primary data was gathered through questionnaires. A pilot study was conducted to test the validity and reliability of the data collection instruments. The data was analyzed both qualitatively and quantitatively through SPSS, results presented in form of tables, and figures. Findings: The findings show that creativity and innovation have a positive and significant effects on the performance of ICT firms as shown by Î² = 0.233 and Sig = 0.010 <0.05. Employee commitment likewise, has a positive and significant effects on the performance of ICT firms as shown by Î² = 0.397 and Sig = 0.001 <0.05. The results further show that corporate image has a positive and significant effects on the performance of ICT firms as shown by Î² = 0.121 and Sig = 0.012 <0.05. In addition, human capital tool has a positive and significant effects on the performance of ICT firms as shown by Î² = 0.406 and Sig = 0.000 <0.05. Unique contribution to theory, practice and policy: The study recommended that the management of ICT firms in Nairobi County should focus on enhancing elements that boost the levels of innovation amongst employees in the firm since the practice bears positive and significant effects on performance of the firm. The study also recommended that the management of ICT firms in Nairobi County should focus on advancing the factors that contribute to increased levels of employee commitment in the firm since the practice bears positive and significant effects on performance of the firm. The study further recommended that the management of ICT firms in Nairobi County should focus on improving the corporate image since the practice bears positive and significant effects on performance of the firm. The study finally recommended that the management of ICT firms in Nairobi County should advance their human capital pool since the practice bears positive and significant effects on performance of the firm.